Single‐Molecule Magnets DyM2N@C80 and Dy2MN@C80 (M=Sc, Lu): The Impact of Diamagnetic Metals on Dy3+ Magnetic Anisotropy, Dy⋅⋅⋅Dy Coupling, and Mixing of Molecular and Lattice Vibrations. Issue 11 (6th February 2020) - Spree, Lukas; Schlesier, Christin; Kostanyan, Aram; Westerström, Rasmus; Greber, Thomas; Büchner, Bernd; Avdoshenko, Stanislav M.; Popov, Alexey A.
Abstract: The substitution of scandium in fullerene single‐molecule magnets (SMMs) DySc2 N@C80 and Dy2 ScN@C80 by lutetium has been studied to explore the influence of the diamagnetic metal on the SMM performance of dysprosium nitride clusterfullerenes. The use of lutetium led to an improved SMM performance of DyLu2 N@C80, which shows a higher blocking temperature of magnetization ( T B =9.5 K), longer relaxation times, and broader hysteresis than DySc2 N@C80 ( T B =6.9 K). At the same time, Dy2 LuN@C80 was found to have a similar blocking temperature of magnetization to Dy2 ScN@C80 ( T B =8 K), but substantially different interactions between the magnetic moments of the dysprosium ions in the Dy2 MN clusters. Surprisingly, although the intramolecular dipolar interactions in Dy2 LuN@C80 and Dy2 ScN@C80 are of similar strength, the exchange interactions in Dy2 LuN@C80 are close to zero. Analysis of the low‐frequency molecular and lattice vibrations showed strong mixing of the lattice modes and endohedral cluster librations in k ‐space. This mixing simplifies the spin–lattice relaxation by conserving the momentum during the spin flip and helping to distribute the moment and energy further into the lattice. Abstract : What a mix ! The diamagnetic metal in DyM2 N@C80 and Dy2 MN@C80 (M=Lu or Sc) has a considerable influence on the single‐molecule magnetism of clusterfullerenes. DyLu2 N@C80 has a higher blocking temperature of magnetization than DySc2 N@C80, whereas exchange coupling in Dy2 LuN@C80 is much weaker than in Dy2 ScN@C80 . The different masses of lutetium and scandium also alter the mixing of local cluster vibrations and lattice modes, and hence have a strong impact on the spin–lattice relaxation (see figure).